AUDIT OPERASIONAL UNTUK MENGEVALUASI EFEKTIVITAS SUMBER DAYA MANUSIA DI CV JAYA SENTOSA - Akhma, Ferry Adjie; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to analyze the effectiveness of human resources management through operating audit and to examine which department who has made the ineffectiveness of the HRD and to give necessary recommendation as the effort to improve and to increase the function of the human resources at CV Jaya Sentosa. This research has been conducted in February 2017 at Jalan Semolowaru Selatan X no. 2 Surabaya. This research has been done by using qualitative descriptive method. The researcher has conducted direct research and the data collection technique has been carried out by conducting interview, issuing questionnaires, and performing direct observation at CV Jaya Sentosa. The result of this research shows that the human resources at CV Jaya Sentosa has been running well. Yet, there are some weaknesses i.e. the work force planning function has not got written and documented work force planning yet and there is no written interview material in the selection function and there is no standardization in the development and training function for the selected employee to be participated in the development is merely based on the employeeâs ability. It has been expected from this research that operating audit can be used as the device to help the human resources to improve the determined procedures and policies in order to make the performance of the human resources can be achieved optimally.Keywords: Audit operational, personal function performance, effectiveness.